PEMBUATAN PATI DARI BIJI DURIAN MELALUI PENAMBAHAN NATRIUM METABISULFIT DAN LAMA PERENDAMAN - Budi Suarti; Misril Fuadi; Bachri Harun Siregar (AGRIUM: Jurnal Ilmu Pertanian, 2013)
This study aims to find the effect of the sodium metabisulfhite and duration in solution for the quality of durian seed flour.  This study uses a Complete Randomized Design (CRD) with factorial of  two reflicates. Factor I is the number of sodium metabisulfhite (N) which consists of four standards are : N0 = 0 %, N1 = 0,1 %, N2=0,2% and N3 = 0,3%. Factor II is the duration in solution which consists of four standards are L1 = 20 minute, L2 = 40 minute,    L3 = 60 minute, and L4 = 80 minute. The parameters  observed include : Yield,  water contents, carbohydrates,color and aromatic. The study results of sodium metabisulfhite different effect highly significant to the yield, kadar air, carbohidrates, color, and  different effect not significant for aromatic. The of duration in solution different effect highly significant to the yield, water content, carbohydrates, color and  different effect is not significant for aromatic. Treatment interaction of sodium metabisulfhite and duration in solution effect is not significant.Keywords : sodium metabisulfit, duration in solution, durian seed flour, carbohidrates